The First Crisis of Social Policy in the Post-Stalinist USSR (1958–1964): Causes, Manifestations, Ways of Overcoming (Based on the Materials of the Lower Volga Region) - Alexey Gumenyuk (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The article provides an analysis of the first crisis of social policy in the USSR in the second half of the 20th century (late 1950s – early 1960s): its causes, manifestations in various spheres of Soviet everyday life, and the effectiveness of various ways to overcome it are evaluated. Methods. The research is based on the use of a set of methodological techniques, including both special methods of historical science (structural-functional, problem-chronological, statistical) and a historical-anthropological approach (or the history of everyday life). Materials. The article is based on factual material extracted from the latest scientific publications, collections of central and local archives, legislative documents, statistical collections, memoirs, and periodicals. Analysis. The involvement of a wide array of data sources made it possible to make a number of observations and determine that the crisis of social policy caused by the aggravation of the shortage of economic opportunities in the Soviet Union in 1958–1964 affected the labor and household daily practices of the Volga people. It became possible to overcome the socio-psychological tension in Soviet society that arose in this way only through the use of economic instruments to improve the efficiency of the functioning of the Soviet economy. Results. It is concluded that the economic reform of 1965 became a reliable way for the Soviet state not only to overcome the crisis situation in the country but also to breathe (unfortunately, for a very short period) new impulses into the socialist economy, which allowed (while preserving the economic development model that had existed in the country since the 1930s) to make the most important step in the creation of the Soviet consumer society.